Metagenomic analysis reveals gut plasmids as diagnosis markers for colorectal cancer - Cai, Zhiyuan; Li, Ping; Zhu, Wen; Wei, Jingyue; Lu, Jieyu; Song, Xiaoyi; Li, Kunwei; Li, Sikai; Li, Man (Frontiers in Microbiology, 2023)
Colorectal cancer (CRC) is linked to distinct gut microbiome patterns. The efficacy of gut bacteria as diagnostic biomarkers for CRC has been confirmed. Despite the potential to influence microbiome physiology and evolution, the set of plasmids in the gut microbiome remains understudied. We investigated the essential features of gut plasmid using metagenomic data of 1,242 samples from 8 distinct geographic cohorts. We identified 198 plasmid-related sequences that differed in abundance between CRC patients and controls and screened 21 markers for the CRC diagnosis model. We utilize these plasmid markers combined with bacteria to construct a random forest classifier model to diagnose CRC. The plasmid markers were able to distinguish between the CRC patients and controls (mean area under the receiver operating characteristic curve (AUC = 0.70) and maintained accuracy in 2 independent cohorts. In comparison to the bacteria-only model, the performance of the composite panel created by combining plasmid and bacteria features was significantly improved in all training cohorts (mean AUCcomposite = 0.804 and mean AUCbacteria = 0.787) and maintained high accuracy in all independent cohorts (mean AUCcomposite = 0.839 and mean AUCbacteria = 0.821). In comparison to controls, we found that the bacteria-plasmid correlation strength was weaker in CRC patients. Additionally, the KEGG orthology (KO) genes in plasmids that are independent of bacteria or plasmids significantly correlated with CRC. In conclusion, we identified plasmid features associated with CRC and showed how plasmid and bacterial markers could be combined to further enhance CRC diagnosis accuracy.